Studi Komparasi Prosedur Olah Gerak Kapal Manual dan Digital (Penerapan Website UPP Kelas III Batang) - Niken Devi Rosita; Hanasti Asyifaa Saputri (Sekolah Tinggi Maritim Yogyakarta, 2023)
Ship movement process is one of the ship's activities in carrying out operations in the port area. The purpose of this study is to determine the comparison of manual motion processing permits and using digital systems and obstacles in the field related to the 2 methods above. The application of manual movement experienced problems related to authorized personnel at the time of document legalization, so that the existence of a digital licensing system through the UPP Class III Batang website was encouraged to facilitate ship operational activities. The website used in this licensing digitization system was under the auspices of the Ministry of Transportation. The research method used wass comparative descriptive research to compare two or more situations with data collection techniques in the form of literature studies, document studies, observations and unstructured interviews. The object in this study was TB movement activities. LLB succeed 22 in November 2021.. The results of the research that the implementation of ship movement permit procedures through the website were effective and supported the smooth operation of the ship.